Stimulus Ekonomi bagi Masyarakat Melalui Program Pemuda Mandiri Membangun Desa (PMMD) - Dicky Abiyan Raya; Khoerul Mulia Fatara (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The aim of this service activity is to provide programs to the community to stimulate the economy of underprivileged communities. The results of the activities carried out are as follows: 1) Preparation stages which include: a) checking data on people who will receive basic necessities; b) verify the data that has been obtained; c) make a journal or schedule for outreach and field observations; and d) use existing data as a guide during observation and counseling. 2) Implementation stages which include: a) going directly into the field to several houses to provide health education and training for the community; b) go directly to the field to distribute free basic necessities and provide guidance on the dangers of Acute Respiratory Infections (ARI); and c) re-screen all aid recipients who are deemed not on target.